Global Research Trends and Knowledge Structure of Integrated Sustainable Waste Management: Insights from a Decade of Bibliometric Evidence - Rita Ambarwati (Industrial and Domestic Waste Management, 2026)
The growing complexity of waste governance has positioned Integrated Sustainable Waste Management (ISWM) as an important research domain within global sustainability studies. Although scholarly attention to ISWM continues to increase, a consolidated understanding of publication trends, disciplinary coverage, country contributions, and thematic structures remains limited. This study conducts a bibliometric analysis of ISWM research indexed in Scopus from 2015 to 2025. A total of 465 documents were retrieved using predefined search criteria. The data were cleaned and harmonized using Bibliomagika and OpenRefine, while VOSviewer was used to visualize bibliometric patterns. The results show that journal articles dominate the dataset, accounting for 55.70% of publications, followed by conference papers (20.22%) and book chapters (12.26%). English is the predominant publication language, representing 98.49% of the dataset, whereas Chinese and Korean each account for 0.43%, and German, Italian, and Persian each represent 0.22%. India records the highest publication output with 298 documents, followed by Indonesia (149) and Italy (98). Environmental Science is the leading subject area, accounting for 64.09% of publications, followed by Engineering (29.46%) and Energy (26.67%), with additional contributions from Social Sciences, Computer Science, Business, Economics, Agriculture, Chemistry, Medicine, and other fields. Keyword analysis identifies Waste Management as the most frequently occurring term (104 documents), followed by Sustainability (55 documents). These findings indicate that ISWM has evolved into an interdisciplinary field, with Environmental Science, Engineering, and Energy forming its primary knowledge base.